Rapid on-site identification of the biocontrol agent of the Asian chestnut gall wasp. Issue 9 (1st September 2016) - Colombari, F.; Villari, C.; Simonato, M.; Cascone, P.; Ferracini, C.; Alma, A.; Guerrieri, E.; Battisti, A.
ABSTRACT: In classical biocontrol programmes, a rapid and correct identification of the introduced antagonist is a key issue during both the release and establishment monitoring phases. It is often difficult to distinguish morphologically cryptic species or immature stages. An accurate diagnosis can now be provided by molecular diagnostic methods. Among the conventional and real-time PCR-based methods, loop-mediated isothermal amplification (LAMP) is a particularly suitable technique as it allows a rapid amplification of target DNA directly in the field. During the programme implemented in Italy against the Asian chestnut gall wasp (ACGW) Dryocosmus kuriphilus, we developed a real-time LAMP assay, combined with a simple DNA extraction method, for rapid in-field identification of larvae, pupae, and adults of the biocontrol agent, the parasitoid Torymus sinensis . Validation of the assay comprised adults as well as preimaginal stages of parasitoids obtained from ACGW galls collected from different localities. Results confirmed the effectiveness of the LAMP assay to rapidly and specifically identify the target parasitoid in the field. This assay will be a valuable tool for quick on-site checking of the parasitism rate.